Spatial Heterogeneity of Planning Influencing Factors on Residents’ SWB in Historic Conservation Area of China: Three Cases from Yangzhou - Yue Chen; Yiting Shen; Can Wang (Land)
Cultural heritage conservation planning in China advocates for differentiated planning measures tailored to different heritage elements with diverse values, functions, and locations. However, limited research has focused on the spatial heterogeneity of these multi-dimensional planning measures and the subjective well-being (SWB) of residents within these protected historic districts. This study investigates the spatial differentiation pattern and mechanism of residents’ SWB in three Historic Conservation Areas of Yangzhou, China, by employing a combination of spatial data digitization and data spatialization methods. The findings reveal: (1) All three cases demonstrate notable spatial differentiation in terms of residents’ SWB; (2) A common feature across the three cases is that strengthening community participation, tourism traffic control, and housing improvement projects can significantly improve residents’ SWB. But proximity to historic buildings has little explanatory power for the spatial differentiation of residents’ SWB; (3) Planning factors of traffic accessibility, public facility accessibility, park service areas, and NIMBY areas of public toilets, have significant spatial heterogeneous effects on residents’ SWB across the three cases, which are closely correlated to the varying degrees of tourism development within each district. The findings of this study provide targeted planning strategies for historic districts with different functional orientations and heritage conservation duties, aimed at more effectively enhancing the well-being of heritage site residents by utilizing limited public resources.